Nuevas estrategias docentes en Histología. Más aprendizaje y menos enseñanza: Uso de microscopios virtuales e Historrelatos. - Sánchez-Varo, Raquel María; Escamilla-Sánchez, Alejandro; Bermúdez-Flores, Diego Teófilo; López-Villodres, Juan Antonio (My University, 2023)
Current teaching at the University needs novel methodologies to increase students’ motivation. Here, we present two approaches to engage the student body to Human Histology subject at the University of Malaga. Virtual teaching was propelled by the COVID-19 crisis and confinement. The software for the study of histological/histopathological samples has become a valuable tool. Moreover, digital competences are in high demand within the biomedical field but students usually do not receive sufficient training. For these reasons, we have implemented the use of virtual microscopy (VM, Olympus), sharing 66 digitalized slides accessible under a username/password. VM provides real-time dynamic microscopy and offers an innovative experience at exceptionally high resolution. VM allows students to explore the samples online from anywhere, favoring autonomy and self-learning. Moreover, VM enables capturing specific tissue areas using these pictures to ask specific questions. On the other hand, transversal competences such as reading and writing skills, along with synthesis capability can be underdeveloped in our students. We initiated the activity of writing stories about histology contents (Histostories). Professional graphic designers from a webpage of scientific divulgation (masscience.com) illustrated the first story about erythrocytes. We conducted a survey among medical students to analyze the impact of this narration on their learning. Most of them welcome the initiative, considering it as an appropriate and enjoyable instrument for summarizing and revising the concepts. Immunity was among the topics more demanded between the students. Finally, we encouraged our students to write their own Histostories mentored by our teaching staff. These stories are shared through the virtual campus and on masscience website. So far, two medical students are collaborating with us in this experimental project that we expect it will bring more benefits to both readers and participants.
Keywords: Histología - Estudio y enseñanza superior; Enseñanza -- Innovaciones; Microscopios electrónicos; Docencia; Microscopio virtual; Historrelatos